(untitled) (Torani Journal of Fisheries and Marine Science, 2016)
This study aims to determine the character of the waves, bathymetry, currents and tidal in 2012 in East Kutai. Significant wave height derived from AVISO, satellite altimeter TOPEX/POSEIDON, Jason 1 and Jason 2. Water depth data obtained from the C-MAP Norway map with a scale of 1: 250,000. Monthly surface current data obtained from JODC. Ebb tidal predictions obtained from DISHIDROS Navy. Wave data processing method using the ODV and processed with Surfer 8. Bathymetry visualized in 3D and 2D using Surfer 8 and ArcGIS 10. Distribution of surface currents visualized with Surfer 8 wherein the interpolation process previously performed on each cell domain area and conducted breakline on the cell data is mainland. Results showed that the wave pattern follows the seasonal wind patterns. Waves in the sea around the waters off of East Kutai have a height ranging from 0.45 - 0.66 meters. High waves occur in the east of the season (July - August) where geographically these waters open to the east. The depth of the water reaches > 100 m at a distance of 3 miles from the coast, where the exposure to a wider shallow coastal can be seen around the mouth of the Gulf Sangkulirang. Current velocity relatively strong in March flows ranged from 0.13 - 1.75 m/sec with an average of 1.32 m/sec. Generally move in the direction of flow from north to south following the pattern-oriented morphology North Makassar Straits - south. Type tides are "mixed tide prevailing semidiurnal", where in one day occurred twice ups and downs twice with different heights and periods. Keywords: wave, bathymetry, currents, tidal